Determining the Effect of Covid-19 Disease on Family Physicians` Social and Daily Activities in Kayseri/Türkiye: - Afşin, Ahmet (Opšta medicina, 2022)
Objective: We aimed at determining the effects of Covid-19 disease on family physicians` (FPs) daily work and life.Methods: We searched for GPs who had Covid-19 bymaking inquiries in the Medical Chamber, Association ofGPs in Kayseri, and local health authorities. Our study periodcovers the first year of the Covid-19 pandemic in Türkiye(March 11th, 2020 – March 11th, 2021). The descriptivecharacteristics, we looked into, were the use of preventivemeasures, location of family health centers, the transmissionroute of Covid-19, the symptoms they experienced, FP’s generalhealth status, and additionally details of isolation, diagnosis,and hospitalization procedures.Results: A total of 85 FPs (18.2% of all FPs in the Kayseriregion) had Covid-19 in the first 12 months of the Covid-19 pandemic in Kayseri/Türkiye. FPs who gave consentto participate in our study made up 60.8% of Kayseri`s FPs.Washing hands, keeping distance, using face masks, and frequentindoor ventilation were the most frequently used measures(>75%). More than 2/3 of FPs stuck to the preventivemeasures. The most frequent symptoms experienced by theFPs were muscle and joint pain, weakness, and fever (morethan 1/5 of FPs, respectively 35.4%, 30.4%, 29.1%). Thetransmission sites were mostly Family Health Centers.Conclusion: About 1/6 of FPs were infected with Covid-19. Almost all of them were working in the urban area.The mean hospitalization stay was 7.7 days and in more than50% the symptoms of fever and cough were detected. Thedisease transmission was the most prevalent at the workplaceand the most common concern of FPs was the protection oftheir families.
Keywords: Covid-19; general practitioner; family physician; social activities